Ketika Agama dan Masyarakat Digital Menjadi Senjata Baru Propagada Politik - Safutra Rantona; Asmaul Husna (Jurnal Sosiologi Agama, 2018)
Nineteen months have passed, but the action of the political religious social movements which born post religious sacrilege case on Elections Jakarta turned out to be far from over. The movement originally was a step of consolidation in order to evoke the political consciousness of Muslims, now began to be infiltrated by other groups with particular interests. These interest groups considered to sharpen the conflict and cause the political noise never ended across this country. This article try to expose how the social-political issues played massif and structured in virtual spaces by interest groups in order to form the force and gained the power of politics. And how the relationship between religion, state, and people are pitted in order that the collective identity look sharper. So no wonder that the people of Indonesia now seems to have split in two major axis, Religious versus Nationalist.Sembilan belas bulan telah berlalu, namun aksi dari gerakan sosial politik religius yang lahir pasca kasus penistaan agama pada Pilkada DKI Jakarta ternyata belumlah usai. Gerakan yang semula merupakan sebuah langkah konsolidasi guna membangkitkan kesadaran politik umat islam, kini mulai ditunggangi oleh kelompok lain dengan kepentingan tertentu. Kelompok kepentingan inilah yang ditengarai memperkeruh konflik dan menyebabkan kegaduhan politik tak kunjung usai di seantero negeri. Artikel ini mencoba memaparkan bagaimana isu-isu sosial politik kemudian dimainkan secara massif dan terstruktur dalam ruang-ruang virtual oleh kelompok kepentingan guna membentuk kekuatan politik dan demi meraih kekuasaan. Serta bagaimana relasi antara agama, rakyat, dan negara dibenturkan agar identitas kolektif terlihat lebih tajam. Maka tak heran jika kini rakyat Indonesia seolah telah terpropaganda dan terbelah dalam dua poros besar, Agamis dan Nasionalis.